MSME Development Strategy through Branding Training and Business Digitization by DPPKB in Malang Regency - Natasya A. Putri; Ermita Yusida; Rizal H. U . Nuha (Universitas Brawijaya, 2022)
This activity aims to increase partners' understanding of branding and digital business to strengthen product images and marketing strategies in the digital market. This activity lasted for six weeks in 49 villages with 1,377 participants. The stages of this activity include (1) identification of partner problems, (2) branding training and business digitization, (3) creating social media and e-commerce accounts, (4) making packaging and logo designs, (5) monitoring and evaluation, and (6) activity report. The results of this activity are that 61% of all participants understand the importance of social media, 59% of participants understand the importance of branding, 55% of participants understand the importance of e-commerce, 50% of participants understand social media, 48% of participants understand the meaning of branding, 47% of participants understand about e-commerce. In addition, 661 of 1,377 participants who previously did not have a social media account now have one, and 1,063 participants who previously did not have an e-commerce account now have one.